Pharmacokinetics and pharmacodynamics of a recombinant fusion protein linking activated coagulation factor VII with human albumin (rVIIa-FP) in patients with congenital FVII deficiency. Issue 1 (1st January 2020) - Gorkom, Britta Laros-van; Holme, Pål André; Joch, Christine; Rogosch, Tobias; Feussner, Annette; McKeand, William; Roberts, John; van Heerde, Waander
ABSTRACT: Objectives: Recombinant fusion protein linking activated factor VIIa to human albumin (rVIIa-FP) is a therapeutic option designed to prevent and treat bleeding events in patients with congenital FVII deficiency with reduced infusion frequency compared to current FVII treatments. This study characterized the pharmacokinetics (PK) and pharmacodynamics (PD) of rVIIa-FP. Methods: A phase I multicenter, randomized, open-label, parallel-arm, single-dose study (NCT02470871) was conducted in nine patients with severe congenital FVII deficiency. Patients received their routine FVII product (30 IU/kg plasma-derived FVII [pdFVII] or 25 μg/kg recombinant activated FVII (rFVIIa) [eptacog alfa]), and were then randomly assigned to receive 100 or 300 μg/kg of rVIIa-FP. Blood samples for PK and PD assessments were drawn up to 48 hr after administration. FVIIa activity was determined using a one-stage clotting assay. PD parameters were derived from thrombin generation testing, using the Nijmegen hemostasis assay. Results: rVIIa-FP showed improved PK compared to rFVIIa, with 2- to 3-fold longer t1/2 and 4- to 8-fold lower clearance. Analysis of PD data showed a sustained suppression of lag time below 4.5 min (upper limit of healthy people) for rVIIa-FP compared to rFVIIa. AUEC and ECmax were similar across the two dose groups of rVIIa-FP and rFVIIa. Discussion : rVIIa-FP was well tolerated in patients with congenital FVII deficiency, showed a longer half-life and lower clearance compared to rFVIIa, and lag time remaining within healthy ranges for ≥8 hr. Conclusion: These results warrant further investigation into the efficacy of rVIIa-FP to control and prevent bleeding in patients with FVII deficiency.